New p-dimensional lattices from cyclic extensions - Lopes Nunes, Jose Valter; Carmelo Interlando, J.; Nobrega Neto, Trajano Pires da [UNESP]; Dantas Lopes, Jose Othon (World Scientific Publ Co Pte Ltd, 2017)
In this work, p-dimensional point-lattices are constructed from a number field L, where L/Q is a cyclic extension of degree p, an odd unramified prime in L/Q. Families of lattices whose packing densities asymptotically approach those of Lambda(p), p = 3, 5, 7, are explicitly exhibited.
Keywords: Cyclic extensions; lattice packing; trace forms of number fields